Pengukuran Ketepatan Alignment Sistem Penjejak Gerak Benda Langit dengan Metode Drift Berbantuan Tracker - Lukmanul Hakim; Yudhiakto Pramudya (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2020)
The simulation of the drift method application using a celestial body tracker has been done. Experiments were carried out by recording the movement of a celestial body tracker with variation orientation of polar angle and azimuth from the true south and polar angle a particular location. The variation is between -2° to +2°. It was found that the greater the difference in the mounting orientation from the true orientation, the greater the shift in altitude and azimuth of the celestial object’s path.